2012
DOI: 10.1590/s1135-57272012000100009
|View full text |Cite
|
Sign up to set email alerts
|

Consumo episódico excesivo de alcohol en adolescentes: su asociación con los estados de ánimo negativos y los factores familiares

Abstract: Negative mood states are associated with heavy episodic drinking. Socio-economic and family factors have stronger effect on women than on men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
(34 reference statements)
3
5
0
Order By: Relevance
“…Regarding age, our findings are consistent with those of other studies [33,[44][45][46] that show that alcohol use, as well as the use of other drugs, increases with age. Moreover, this study showed an association between availability of money and excessive alcohol use, finding that as weekly pocket money increases, so does the likelihood of consuming alcohol.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding age, our findings are consistent with those of other studies [33,[44][45][46] that show that alcohol use, as well as the use of other drugs, increases with age. Moreover, this study showed an association between availability of money and excessive alcohol use, finding that as weekly pocket money increases, so does the likelihood of consuming alcohol.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding age, our findings are consistent with those of other studies [33,[44][45][46] that show that alcohol use, as well as the use of other drugs, increases with age. Moreover, this study showed an association between availability of money and excessive alcohol use, finding that as weekly pocket money increases, so does the likelihood of consuming alcohol.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding age, our findings are consistent with those of other studies [45][46][47][48] that show that alcohol use, as well as the use of other drugs, increases with age. Moreover, this study showed an association between availability of money and excessive alcohol use, finding that as weekly pocket money increases, so does the likelihood of consuming alcohol.…”
Section: Discussionsupporting
confidence: 92%